Peran Waka Kurikulum dalam Implementasi Kurikulum Merdeka Terhadap Perkembangan Belajar Siswa di SMA Muhammadiyah Palembang - Dimas Prayanto Pratama (Educational Journal, 2026)
This study aims to determine the role of the Vice Principal for Curriculum Affairs in the implementation of the Merdeka Curriculum toward students’ learning development at SMA Muhammadiyah Palembang. This study employed a qualitative method with a field observation approach. Data collection techniques were conducted through observation, interviews, and documentation to obtain information regarding the implementation strategies of the Merdeka Curriculum and its impact on the learning process. The results of the study indicate that the Vice Principal for Curriculum Affairs plays an important role in planning, directing, and evaluating the implementation of the Merdeka Curriculum at school. The strategies implemented include Project Based Learning, differentiated learning, and the use of creative and interactive learning media. The implementation of this curriculum has a positive impact on students’ learning development, such as increasing learning motivation, creativity, activeness, and critical thinking skills in the learning process. Although there are several obstacles, such as teacher readiness and limited facilities, the school has made various efforts through training, workshops, and regular evaluations to overcome these challenges. Therefore, the implementation of the Merdeka Curriculum at SMA Muhammadiyah Palembang is considered effective in supporting the improvement of learning quality and students’ learning development